FACS-based immunoassay of troponin-I using E-coli cells with autodisplayed Z-domains - Park, Min; Bong, Ji-Hong; Chang, Young Wook; Yoo, Gu; Jose, Joachim; Kang, Min-Jung; Pyun, Jae-Chul (ROYAL SOC CHEMISTRY, 2014)
Fluorescence-activated cell sorter (FACS)-based immunoassays using E. coli cells with autodisplayed Z-domains were performed to (1) improve the sensitivity of the immunoassay through orientation control of antibodies with autodisplayed Z-domains and (2) minimize the required amount of analyte by using FACS to measure the fluorescent signal from individual E. coli cells. The expression (autodisplay) of Z-domains on the outer membrane of E. coli was confirmed by fluorescence image analysis, and the homogeneous distribution of autodisplayed Z-domains was presented by SEM image analysis after treatment with antibodies labeled with gold nanoparticles (diameter of 15 nm). As FACS measures the fluorescent signal from individual E. coli cells, the optimal FACS parameters for the effective detection of fluorescently labeled E. coli cells were determined, and the minimum amount of analyte required for the E. coli cell-based immunoassay was identified using two model immunoassay configurations. Finally, the medical diagnosis of heart infarction with a biomarker called troponin-I using the E. coli cell-based immunoassay with FACS analysis was demonstrated.